Altered skeletal muscle mitochondrial biogenesis but improved endurance capacity in trained OPA1‐deficient mice. (16th October 2013) - Caffin, F.; Prola, A.; Piquereau, J.; Novotova, M.; David, D.J.; Garnier, A.; Fortin, D.; Alavi, M.V.; Veksler, V.; Ventura‐Clapier, R.; Joubert, F.
Key points:   OPA1 is a mitochondrial protein well known to play a fundamental role in the fusion of the inner membrane, in the organization of mitochondrial cristae and in apoptosis.   Although the function of mitochondrial dynamics is becoming well understood, its impact on mitochondrial biogenesis is poorly studied, especially in differentiated adult tissues.   Here we report a novel finding that in fast skeletal muscles OPA1 deletion impairs training‐induced mitochondrial biogenesis.   However, our data reveal that Opa1 +/− skeletal muscles after training possess better exercise endurance capacity, obviously due to a modification of mitochondrial fatty acid utilization.   Thus OPA1 deficiency induces a unique pattern of adaptation to endurance training in fast skeletal muscles. Abstract  The role of OPA1, a GTPase dynamin protein mainly involved in the fusion of inner mitochondrial membranes, has been studied in many cell types, but only a few studies have been conducted on adult differentiated tissues such as cardiac or skeletal muscle cells. Yet OPA1 is highly expressed in these cells, and could play different roles, especially in response to an environmental stress like exercise. Endurance exercise increases energy demand in skeletal muscle and repeated activity induces mitochondrial biogenesis and activation of fusion–fission cycles for the synthesis of new mitochondria. But currently no study has clearly shown a link between mitochondrial dynamics and biogenesis. Using a mouse model of haploinsufficiency for the Opa1 gene ( Opa1 +/− ), we therefore studied the impact of OPA1 deficiency on the adaptation ability of fast skeletal muscles to endurance exercise training. Our results show that, surprisingly, Opa1 +/− mice were able to perform the same physical activity as control mice. However, the adaptation strategies of both strains after training differed: while in control mice mitochondrial biogenesis was increased as expected, in Opa1 +/− mice this process was blunted. Instead, training in Opa1 +/− mice led to an increase in endurance capacity, and a specific adaptive response involving a metabolic remodelling towards enhanced fatty acid utilization. In conclusion, OPA1 appears necessary for the normal adaptive response and mitochondrial biogenesis of skeletal muscle to training. This work opens new perspectives on the role of mitochondrial dynamics in skeletal muscle cells and during adaptation to stress.